Commentary on Edmund Rolls: "Emotion and reason in human decision-making" - Mark Solms (Kiel Institute for the World Economy (IfW), 2019)
In his paper Emotion and reasoning in human decision-making (Economics Discussion Papers, No 2019-8) Edmund Rolls points out that multiple and independent types of reinforcement exist in the human brain, and that they cannot be reduced to a common currency. The present commentary introduces non-specialist readers to this wide variety of reinforcers, each of which carries equal biological value. The evolutionary forces underwriting them reveal much about the causes of our apparently irrational choices - which is why it is important for economists to acquaint themselves with such things.
Keywords: D01; D87; D91; E71; G41; 330; decision-making; brain mechanisms; basic emotions; reward value; economicvalue; dominance hierarchies; macroeconomics; microeconomics; affective neuroscience